Literature Review: Effectiveness of Chest CT for Triage in the Emergency Departmet (ED) in Patients with Suspected COVID-19 - Aniq Lutfiyah; Iwan Purnawan; Ridlwan Kamaluddin (Journal of Bionursing, 2021)
Background: COVID-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus. The spread of this virus is very fast, so patients come to the Emergency Department (ED) for examination. The initial examination was carried out by triage the patient using the RT-PCR method. Then, there are recent studies that Computed Tomography (CT) can be used as a triage tool and help in the early diagnosis of patients with suspected COVID-19. Objectives: To determine chest CT for triage in the Emergency Department (ED) in patients with suspected COVID-19. Method:Search for articles was conducted electronically using Google Scholar, Sience Direct, and PubMed databases. Article used from March 2020 to January 2021. Keywords in this article search used the keywords "chest CT" for "triage" and "emergency department" for "COVID-19" and "chest x-ray" for "triage" and "emergency department" for "COVID-19", thus getting 5 research articles reviewed. Results: A chest CT that can be used as a triage tool based on the speed at which the chest CT results can be released depicting a confirmed COVID-19 patient in 60 minutes. Second, based on the sensitivity of chest CT there was 90.2% and according to chest CT instructions there was 89%. Conclusion: Chest CT examination is very effective as the first triage in diagnosing patients with suspected COVID-19.